Analisis Regresi Binomial Negatif terhadap Faktor-Faktor yang Memengaruhi Kasus Tuberkulosis di Jawa Barat, Indonesia - Fikriya, Aufa; Shalfa Salsabilla; Raisah Zharifah Labibah; Sri Winarni; Defi Yusti Faidah; Anindya Apriliyanti Pravitasari; Triyani Hendrawati; Irlandia Ginanjar (EKSAKTA: Journal of Sciences and Data Analysis, 2026)
Tuberculosis (TB) remains a major public health problem globally, with West Java reporting the highest number of TB cases among all provinces in Indonesia in 2023. This study aims to identify key factors influencing TB incidence across districts and cities in West Java in 2024. The analysis focuses on healthy living behaviors, proper sanitation, HIV cases, and AIDS cases using a Negative Binomial Regression approach to address overdispersion in count data. The results show that proper sanitation has a significant negative association with TB incidence, while HIV and AIDS cases exhibit significant positive associations. The best-performing model includes these three variables, yielding a residual deviance of 27.615. These findings highlight the importance of integrated public health interventions that simultaneously improve sanitation and strengthen HIV/AIDS control programs to effectively reduce TB incidence in high-burden regions.